Investigation of physico-chemical processes forming the structure of waterresistant composite materials based on modified gypsum binders (Международный научный журнал «Инженер», 2026)
The article presents the results of studies of the physico-chemical processes of forming the structure ofthe material and the development of effective compositions of modified gypsum-carbonate compositegypsum materials based on gypsum binder, microcalcite and modifying polymer additives, contributingto the improvement of their rheological and physico-mechanical properties and, accordingly, to increasethe bending strength of building decorative ceiling suspended gypsum boards based on them. As a result,it became possible to organize the production of ceiling-mounted suspended composite gypsum boardswith high water resistance and physico-mechanical properties and low cost, as well as the widespreaduse of this board in the construction of residential buildings and construction structures in the republic